Jaws from the deep: biological and ecological insights on the kitefin shark Dalatias licha from the Mediterranean Sea - Bottaro, Massimiliano; Sinopoli, Mauro; Bertocci, Iacopo; Follesa, Maria Cristina; Cau, Alessandro; Consalvo, Ivan; Scarcelli, Faustino; Sperone, Emilio; Vacchi, Marino; Marsili, Letizia; Consales, Guia; Danovaro, Roberto (Frontiers in Marine Science, 2023)
Due to their late maturation, extreme longevity, low fecundity and slow growth rates, deep-sea Chondrichthyes are extremely vulnerable to human impacts. Moreover, assessing the impact of deepsea fisheries is difficult, as many species (including sharks) are part of the bycatch and are often discarded at sea, and/or landed under generic commercial-species codes. The lack of this information on fishery data sets, and the limited availability of species-specific life history data makes challenging the management of deep-sea Chondrichthyes. The kitefin shark Dalatias licha is a cosmopolitan elasmobranch, mainly found on continental and insular shelf-breaks and slopes in warm-temperate and tropical waters, it is a common by-catch of the deep-sea trawling is defined "Endangered" by the IUCN Red List, for all European waters, Mediterranean Sea included. Here we present the results of a study based on a total of 78 specimens of kitefin shark collected over 3 years in the Ligurian Sea (NW Mediterranean) as by-catch from deep-water fisheries. Total length ranged from 380 to1164 mm, and individual weight ranged from 198 to 8000 g. Immature and mature individuals of both sexes showed a sex ratio dominated by males. Adult males were observed throughout the year, while mature females were observed only in spring-summer. These data lead to hypothesise a spatial segregation between genders. The kitefin shark diet was dominated by bony fish (mainly Macrouridae) and other small sharks (e.g., Galeus melastomus and Etmopterus spinax), but their gut included plastic items and parasites. Data reported here underline the rarity, complex ecology and the threat for this shark species and support the urgency of promoting initiatives for their monitoring and conservation.